2020
DOI: 10.26809/joa.5.021
|View full text |Cite
|
Sign up to set email alerts
|

Koronavi̇rüs (Covi̇d-19) Süreci̇nde Uzaktan Eği̇ti̇mi̇n Turi̇zm Li̇sans Öğrenci̇leri̇ Tarafindan Değerlendi̇ri̇lmesi̇

Abstract: Bu çalışmada Covid-19 sürecinin internet tabanlı uzaktan eğitimi zorunlu kılması sebebiyle bu eğitim yöntemi hakkında turizm öğrencilerinin görüşlerinin tespit edilmesi ve buradan hareketle internet tabanlı uzaktan eğitim sisteminin değerlendirilmesi amaçlanmıştır. Bu bağlamda çalışmanın verileri, Çanakkale Onsekiz Mart Üniversitesi, Turizm Fakültesi lisans eğitimi bahar dönemi uzaktan eğitim ders süreci olan 21 Mart-24 Nisan 2020 içerisindeki süreçte toplanmıştır. Araştırma sonuçlarına göre, Çanakkale Onsekiz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0
9

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(22 citation statements)
references
References 4 publications
1
8
0
9
Order By: Relevance
“…Although this result supports the literature [18][19][20][21], there are also studies in which participants have positive [22] and negative views on distance education [23,24].  Although there are studies in the literature showing that male participants have more positive opinions about distance education [25,26] or that there is no significant difference in terms of gender [27], our research results show that female participants have more positive views.  Approximately half of the academicians participating in the study (48.4%) stated that students did not participate in the lessons taught by distance education, and the vast majority (67.7%) thought that students were not as active as the formal education lessons in these lessons.…”
Section: Conclusion and Suggestionssupporting
confidence: 78%
See 1 more Smart Citation
“…Although this result supports the literature [18][19][20][21], there are also studies in which participants have positive [22] and negative views on distance education [23,24].  Although there are studies in the literature showing that male participants have more positive opinions about distance education [25,26] or that there is no significant difference in terms of gender [27], our research results show that female participants have more positive views.  Approximately half of the academicians participating in the study (48.4%) stated that students did not participate in the lessons taught by distance education, and the vast majority (67.7%) thought that students were not as active as the formal education lessons in these lessons.…”
Section: Conclusion and Suggestionssupporting
confidence: 78%
“…Data on the demographic characteristics of the participantsAs seen in Table1, the academians who participated in the survey consisted of 42 female and 51 male. Again, 28 of the participants are between the ages of[23][24][25][26][27][28][29][30][31][32][33] 38 are between the ages of 34-44 and 27 are the ages 45 and over. Looking at the titles of the participants, there are 30 Lecturer, 11 Lecturer Dr., 26 Assistant Prof., 16 Associate Prof. and 10 Professors.…”
mentioning
confidence: 99%
“…In the current study; no difference existed in attitudes towards e-learning in terms of pre-service teachers' gender (Table 3), which was consistent with the results of other studies in the literature (Kar, Saha, & Mondal, 2014;Topal, 2016;Korucu, Usta, & Çoklar, 2019;Altuntaş Yılmaz, 2020;Karadağ & Yücel, 2020;Mavi & Erçağ, 2020). However; the study of Haznedar (2012), which was carried out with university students from different universities prior to the pandemic argued that male students' attitudes towards e-learning were higher than those of female students; the study of Buluk and Eşitti (2020) which was conducted with undergraduate students attending the department of tourism management during COVID-19 pandemic, found that male students were more satisfied with distance education courses as compared to female students, and attended the activities of distance education courses more. And the study of Aktaş, Büyüktaş, Gülle, and Yıldız (2020) identified that male students preferred courses to be offered through distance education more than did female students during both the COVID-19 pandemic period and the previous normal period.…”
Section: Gender and Pre-service Teachers' Attitudes Towards E-learningmentioning
confidence: 99%
“…Ġstanbul ġubesi, 2020;KAYUZEM, 2020;Selçuk Üniversitesi, 2020;Ġstanbul ODTÜ Mezunları Derneği, 2020;Ġstanbul Üniversitesi, 2020;Van Yüzüncü Yıl Üniversitesi, 2020;Metin A. E., Karaman A. ve ġaĢtım Y. A., 2017;Kürtüncü M., Kurt A., 2020;Yılmaz Ö., Özkan B., 2014;AfĢar B., Büyükdoğan B., 2020;Saltürk A., Güngör C., 2020;Karadağ E., Yücel C., 2020;Gören S. Ç., Gök F., Yalçın M., Göregen F., ÇalıĢkan M., 2020;Korkmaz A., 2016;Yılmaz Ö., Özkan B., 2014;AltuntaĢ Yılmaz N., 2020;Buluk B., EĢitti B., 2020. Yapılan çalıĢmalar incelenmiĢ, ana hat olarak 9 soruya verilen cevapların ortalamaları alınmıĢtır.…”
Section: Türkiye'de Yapılan Anket çAlıģmalarından Derlemelerunclassified